2003
DOI: 10.1038/nature01450
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity in two-dimensional CoO2 layers

Abstract: Since the discovery of high-transition-temperature (high-T(c)) superconductivity in layered copper oxides, many researchers have searched for similar behaviour in other layered metal oxides involving 3d-transition metals, such as cobalt and nickel. Such attempts have so far failed, with the result that the copper oxide layer is thought to be essential for superconductivity. Here we report that Na(x)CoO2*yH2O (x approximately 0.35, y approximately 1.3) is a superconductor with a T(c) of about 5 K. This compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

53
1,470
4
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,811 publications
(1,531 citation statements)
references
References 5 publications
53
1,470
4
4
Order By: Relevance
“…7.2.2. Na x CoO 2 ·yH 2 O The water-intercalated cobalt oxide superconductor Na x CoO 2 · yH 2 O consists of thick insulating layers of Na ions and H 2 O molecules separating superconducting CoO 2 layers and has a T c of about 5 K [178]. This material has many similarities to the high-temperature cuprate superconductors, but also disparities; the Co ions form a triangular lattice, there are multiple bands around the Fermi level, and the system has a filling level far from half-filling.…”
Section: Srptasmentioning
confidence: 99%
“…7.2.2. Na x CoO 2 ·yH 2 O The water-intercalated cobalt oxide superconductor Na x CoO 2 · yH 2 O consists of thick insulating layers of Na ions and H 2 O molecules separating superconducting CoO 2 layers and has a T c of about 5 K [178]. This material has many similarities to the high-temperature cuprate superconductors, but also disparities; the Co ions form a triangular lattice, there are multiple bands around the Fermi level, and the system has a filling level far from half-filling.…”
Section: Srptasmentioning
confidence: 99%
“…The de-intercalation and hydration of the layered sodium cobalt oxide Na x CoO 2 through an oxidation and subsequent hydration reaction results in the bilayer hydrate Na 0.3 CoO 2 ·1.4H 2 O, which is superconducting below 4~5 K [1]. An alternative synthesis route to make the superconductive Na 0.3 CoO 2 ·1.4H 2 O using aqueous Na 2 S 2 O 8 instead of Br 2 in acetonitrile and subsequently re-hydrating was introduced in a previous report [2].…”
Section: Introductionmentioning
confidence: 99%
“…Pellets were pressed at only moderate pressures (less than 10,000 pounds per square inch) to prevent dehydration of the superconducting phase. Powder X-ray diffraction studies indicated that the samples consisted solely of the superconducting Na x CoO 2 ·1.3H 2 O structure type (1,8).…”
mentioning
confidence: 99%
“…The crystal structure of Na 0.3 CoO 2 ⋅1.3H 2 O consists of electronically active triangular CoO 2 layers separated by spacer layers of sodium and water (1). The triangular CoO 2 lattice and the speculation that it might be a Mott-Hubbard insulator has made this superconductor of particular interest to theorists (2)(3)(4)(5)(6)(7).…”
mentioning
confidence: 99%